2002
DOI: 10.1046/j.1469-0705.2002.00684.x
|View full text |Cite
|
Sign up to set email alerts
|

Fetal pulmonary venous flow pattern is determined by left atrial pressure: report of two cases of left heart hypoplasia, one with patent and the other with closed interatrial communication

Abstract: We report two cases of fetal left heart hypoplasia with extremes of size of interatrial communication, i.e. a closed foramen ovale and an atrial septal defect. Doppler examinations of the pulmonary veins showed almost to and fro flow in the fetus with the closed foramen ovale and, in contrast, a normal flow velocity waveform in the fetus with the atrial septal defect, despite mitral atresia. Our observations support the importance of left atrial pressure in the creation of a pulmonary venous flow pattern in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2002
2002
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Our three types of PV flow patterns likely represent a continuum in the degree of LA hypertension, with progressively decreasing early diastolic forward flow and increasing a-wave reversal with worsening LA hypertension. The short, very pulsatile, to-and-fro flow PV flow pattern has only been previously demonstrated in an isolated case report of fetal HLHS with an intact atrial septum (25). The fact that differences in the degree of a-wave reversal observed in type A and B flow patterns did not result in significant clinical differences may reflect only more subtle but not clinically relevant differences in LA pressure, as well as the influence of other variables on PV flow patterns (18,(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Our three types of PV flow patterns likely represent a continuum in the degree of LA hypertension, with progressively decreasing early diastolic forward flow and increasing a-wave reversal with worsening LA hypertension. The short, very pulsatile, to-and-fro flow PV flow pattern has only been previously demonstrated in an isolated case report of fetal HLHS with an intact atrial septum (25). The fact that differences in the degree of a-wave reversal observed in type A and B flow patterns did not result in significant clinical differences may reflect only more subtle but not clinically relevant differences in LA pressure, as well as the influence of other variables on PV flow patterns (18,(21)(22)(23)(24).…”
Section: Discussionmentioning
confidence: 92%
“…Altered systemic venous flow patterns with increasing a-wave reversal have been shown to correlate with increased right atrial pressures in adults (16) and fetuses (17). Increased a-wave reversal in the pulmonary veins (PVs) has been shown to reflect LA hypertension in adults (18 -24), and preliminary work suggests that it may also reflect LA hypertension in fetal HLHS (15,25). In the present study, we sought to determine whether direct FO measurements and PV patterns correlate with postnatal FO restriction, clinical evidence of LA hypertension, and outcome after birth.…”
mentioning
confidence: 98%
“…Prominent flow reversal in dilated pulmonary veins indicated LA hypertension in all 7 fetuses despite the presence of small decompressing veins in 2 ( Figure 1). 13,14 Two fetuses were hydropic at diagnosis. Three of the fetuses had a small LA with a thick atrial septum, whereas the others had a thin septum bowing into the right atrium.…”
Section: Methodsmentioning
confidence: 99%
“…Changes in fetal pulmonary venous Doppler (PVD) flow patterns in the setting of left heart obstruction, reflective of left atrial hypertension, 12,13 are now routinely demonstrable by pulsed Doppler evaluation on fetal echocardiography. [13][14][15][16] Moreover, it has been demonstrated that in the fetus with left heart obstruction and RAS, there are changes in pulmonary venous flow patterns 13 associated with the need for emergent atrial septoplasty (EAS) in the newborn period.…”
mentioning
confidence: 99%